PS-051 Pharmaceutical validation: a necessary approach in oncology clinical trials units. (25th February 2017) - Mora, P; Gary, C; Tamisier, S; Djabarouti, S; Xuereb, F; Breilh, D
Abstract : Background: The necessity of pharmacist validation for patient safety and risk management is well established. We previously published an instrument for the documentation of pharmaceutical interventions (PIs) specific to oncology (FIPO) 1 based on the pharmacist intervention form published by the French Society of Clinical Pharmacy. Few communications about the pharmaceutical validation in clinical research are available; none of them concern PIs. Purpose: The aim of this study was to describe the PIs on experimental drug prescriptions in oncology. Material and methods: A 3 month prospective observational study was performed. Clinical trials prescriptions in oncology were analysed using the computerised physicians order entry CHIMIO and the patient medical file. Identification of drug related problems (DRPs), the pharmacist's intervention and their future were categorised according to our validated pharmacist interventions form, FIPO. Results: In 387 prescriptions analysed, 31 interventions were performed (8%). DRPs identified were wrong patient biological and/or physiological data (6.5%), inappropriate drug prescribed (19.5%), inappropriate arm of treatment (13%), untreated indication (3%), subtherapeutic or supratherapeutic dosage (48.5%) and improper administration (9.5%). The pharmacist's interventions were recommendation of patient data modification (6.5%), drug switch (32.5%), dose adjustments (48.5%), addition of a new drug (3%) and administration mode optimisation (9.5%). The acceptance rate by clinicians reached 90% (n=28). Among the 3 unaccepted interventions, 2 concerned an improper administration (inappropriate timing of administration) and were considered as protocol deviations compromising the participation of the patient in the clinical trial. Conclusion: The critical nature of observed DRPs should be understood not only from a clinical impact point of view. Indeed, the impact of medication errors in clinical trials can vary from lack of statistical power compromising data analysis to patient exclusion. Avoiding them is one of the pharmacist's missions, so that we need to improve pharmaceutical validation and make it easier by developing multidisciplinary software specifically adapted to clinical research. References and/or acknowledgements: 1. Gary C, et al. Validation of a specific tool elaborated for coding pharmaceutical interventions in oncology. Eur Congress of Oncol Pharm 2016. No conflict of interest